2013
DOI: 10.1016/j.breast.2013.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of breast cancer mortality trends in Europe

Abstract: a b s t r a c tObjectives: To identify patterns of variation in breast cancer mortality in Europe (1980e2010), using a model-based approach. Methods: Mortality data were obtained from the World Health Organization database and mixed models were used to describe the time trends in the age-standardized mortality rates (ASMR). Model-based clustering was used to identify clusters of countries with homogeneous variation in ASMR. Results: Three patterns were identified. Patterns 1 and 2 are characterized by stable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 54 publications
0
25
0
3
Order By: Relevance
“…The mean overall participation was 67.0% [35]. Spain currently has a lower BC mortality rate among the European countries [18,36]. Undoubtedly, the coverage of BC screening has been successful and screening should be used in other diseases when possible.…”
Section: Discussionmentioning
confidence: 99%
“…The mean overall participation was 67.0% [35]. Spain currently has a lower BC mortality rate among the European countries [18,36]. Undoubtedly, the coverage of BC screening has been successful and screening should be used in other diseases when possible.…”
Section: Discussionmentioning
confidence: 99%
“…During the last few decades, survival has improved as a result of earlier diagnoses and the use of more effective and aggressive treatments [2], surpassing 80% in most developed settings [3]. The growing number of women living for longer periods with potential sequelae of breast cancer treatment makes it the worldwide leading cause of years lived with disability due to oncological diseases in women [4], which highlights the need of a comprehensive assessment of the burden associated with breast cancer treatment among survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Others reported that a significant association was observed between early onset of menarche and risk of luminal disease (Millikan et al, 2008). Moreover, there were no significant differences associated with other reproductive factors such as parity, age at first live birth, breastfeeding history, age at menopause, or synthetic hormone use (Yanhua et al, 2012;Amaro et al, 2013).…”
Section: Discussionmentioning
confidence: 99%